(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The origin of the lowest Varna of Hindu society might have been outside the pale of the Aryan society. Since then, it has been held that the fourth Varna was mainly formed by the non-Aryan population, who were reduced to that position by the Aryan conquerors. It has been argued that the Dasas and Dasyus were non-Aryan, must be speaking different language and having a different life style. They were organized in to tribe called Vish. In post Vedic period, Sudras appear mainly as the serving class. They held independent property in cattle, which seems still to have been the chief form of wealth, may not have been under the necessity to serve upper classes. Manu even mentions Sudra teachers and pupils, showing that the Sudra was not denied the right to learning.But the Jaiminiya Brahmana refers Sudra as serving class, who is created from the feet of Prajapati. In this article I will highlight their postion in society.